Age Dynamics and Adaptive Changes in Children Aged 10-12 Years Under the Influence of Athletics (Texas Journal of Multidisciplinary Studies, 2022)
The motor abilities of children and adolescents are very closely related to their morphological and functional characteristics, specific for each age group. Track and field athletics are a good prevention of various diseases of the musculoskeletal system (flat feet, poor posture, scoliosis), respiratory and cardiovascular systems, have a beneficial effect on metabolic processes, increase the body's defenses. In this regard, this article shows the functional changes and age dynamics of young children in this area.